Use of acellular dermal matrix xenograft in reconstructive plastic surgery - Luiz Gustavo Balaguer Cruz (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Complex wounds pose a challenge to the plastic surgeon. In these cases, the most common solution is skin grafting or the use of flaps; however, depending on the affected structure, the results may not be satisfactory. Matrices were initially developed for the treatment of burn sequelae. Since then, different varieties of matrices have been developed for application in the treatment of several diseases, including complex wounds. Only a few heterologous acellular dermal matrices (HADMs) are available in Brazil, and they are still very expensive. The objective of this study was to report the experience with the use of HADMs for the treatment of patients with a need for reconstructive plastic surgery. METHOD: From February 2011 to July 2014, five different HADMs were used in the treatment of 24 lesions of different etiologies, including three etiologies not previously described in the literature: rhinophyma, hidradenitis suppurativa, and Lyell's syndrome (toxic epidermal necrolysis). RESULTS: Twenty patients with lesions of different etiologies and who received treatment with HADM grafts in different anatomical regions, associated or not with autologous skin grafting, attained adequate aesthetic and functional results. CONCLUSION: The use of HADMs can be considered an alternative in the treatment of several difficult-to-treat cases, and has its place in modern plastic surgery; however, its indication should be carefully evaluated owing to the high cost of the materials.